WORK DISCIPLINE AND MOTIVATION ON JOB SATISFACTION - Syardiansah Syardiansah; Riny Chandra; Ayu Lestari (UNIVERSITAS PGRI MADIUN, 2024)
This research aims to determine the influence of work discipline and motivation on job satisfaction of the Satpol PP and Wilayatul Hisbah East Aceh units. The samples in this research were 81 employees in the Satpol PP and Wilayatul Hisbah East Aceh units. Data were analyzed using multiple liner regression tests, t tests, F tests, normality tests, heteroscedasticity tests, classical assumption tests and hypothesis tests. Based on the results of the t test, it was found that work discipline had a positive and significant influence on job satisfaction, motivation had a positive and insignificant influence on job satisfaction. And the results of the F test show that work discipline and motivation simultaneously have a positive and significant effect on job satisfaction. From the results of the coefficient of determination test, it was found that 43% of the work discipline and motivation variables could explain the job satisfaction variable, while the remaining 57% could be explained by other variables that were not included in this research such as work environment, compensation, etc.